Improving Students’ Listening Skill Through Shadowing - Mukminatus Zuhriyah (IAIN Salatiga, 2016)
Listening is the first part of language skills that everyone gets when learning a language. It comes before speaking, reading, and writing. Meanwhile, most of the students get difficulty to learn listening of a foreign language, especially English. That is why shadowing was applied in the listening class as one of the solutions to make the learners of English listening easy to understand what the speaker says. This collaborative classroom action research was generally to know whether or not shadowing could improve the students listening skill. It was also specifically to know: (1) the lecturer’s activities, (2) the students’ activities, and (3) the students’ responses during the implementation of shadowing in the listening class. The subjects were 18 students of the third semester of English department of education faculty of Hasyim Asy’ari university (UNHASY) Tebuireng Jombang in the academic year of 2016/2017. The data were obtained from the observations got from the notes written by the collaborator and the listening test. The students’ listening skill improved after the implementation of shadowing. It could be seen in the improvement of mean score, from 74.2 in cycle one to 75 in cycle two. Then, the precentage of students passing the minimum mastery criteria also improved, from 61% in cycle one to 77.8% in cycle two. Thus, it can be concluded that shadowing could improve students’ listening skill.